ANALISIS PENERIMAAN RETRIBUSI PASAR DI KABUPATEN KLATEN - Isnaini Kusnindar (Jurnal Administrative Reform, 2017)
This research aims to analyze the relationship and the influence of Human Resources, economic growth and potential retribution to acceptance of retribution market in the district of Klaten. The data used in this research is secondary data from Dinas Perindustrian, Perdagangan, Koperasi dan Usaha Kecil Mikro Menengah including data management market, Human Resource Data and Gross Regional Domestic Product. The population in this study is a traditional market in Klaten regency as many as 50 markets. Testing is done by using a multiple linear regression analysis. The analysis shows that the potential retribution significant and positive impact to acceptance of retribution market in the district of Klaten. While human resources and economic growth has no significant effect and has an inverse relationship the market acceptance of retribution.